2004
DOI: 10.1002/j.1467-8438.2004.tb00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Grief and Mental Health: A Systemic, Contextual and Compassionate Analysis

Abstract: Although not always named, grief is central to the experience of mental illness — for people diagnosed, their families and their friends. Yet grief is almost absent from the literature and practice of mainstream psychiatry. This curious fact led to the writing of this article by two workers and a carer, with editorial and political advice from a consumer, as a small step in the direction of integrating perspectives of workers, carers and consumers. It examines the nature of grief associated with mental illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
0
15
0
3
Order By: Relevance
“…Commentaries by health professionals and consumers (e.g., Ellis 1989;MacGregor 1994;McElroy 1987;Parker 1993;Wasow 1995;Young et al 2004) suggest that parents' grief may be associated with a profound sense of loss; loss of their premorbid, healthier child, loss of hopes and dreams for their child's future, loss of former familial relationships, loss of perceived parental competence and loss of security and certainty. Some have suggested that such grief does not abate over time; rather, it intensifies and remits as parents are continuously confronted by reminders of the discrepancy between what they hoped their child would be and what their child has become (Davis and Schultz 1998;Parker 1993).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Commentaries by health professionals and consumers (e.g., Ellis 1989;MacGregor 1994;McElroy 1987;Parker 1993;Wasow 1995;Young et al 2004) suggest that parents' grief may be associated with a profound sense of loss; loss of their premorbid, healthier child, loss of hopes and dreams for their child's future, loss of former familial relationships, loss of perceived parental competence and loss of security and certainty. Some have suggested that such grief does not abate over time; rather, it intensifies and remits as parents are continuously confronted by reminders of the discrepancy between what they hoped their child would be and what their child has become (Davis and Schultz 1998;Parker 1993).…”
Section: Introductionmentioning
confidence: 98%
“…Much of the research concerning families' experience of their loved one's mental disorder has focused on the many burdens, both objective and subjective, with which parents, siblings, spouses, children and other family members of a mentally ill relative are faced (e.g., Hatfield 1978;Lefley 1996;Maurin and Boyd 1990;Rose 1996;Solomon and Draine 1995;Thompson and Doll 1982). Indeed, families are often encumbered with problems associated with their relative's illness; such as, coping with symptoms of the disorder (e.g., positive and negative symptomatology, mood disturbance, disruptive, socially inappropriate or potentially harmful behaviors), increased caregiving responsibilities, disruptions to family life (e.g., financial hardships, strained relationships, employment difficulties, compromised social life, impaired physical and psychological well-being), adjusting to shortcomings of the mental health system and coping with oppressive social stigma surrounding mental illness (Baronet 1999;Grad and Sainsbury 1968;Gubman and Tessler 1987;Hatfield 1978;Lefley 1996;Maurin and Boyd 1990;Noh and Avison 1988;Young et al 2004). In addition to these hardships, families often experience marked personal suffering in relation to their relative's condition, which is often characterized by stress, exhaustion, worry, sadness and strain (Lefley 1996;Maurin and Boyd 1990;Montgomery et al 1985;Reinhard and Horwitz 1995;Young et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Missed opportunities, an uncertain future, the loss of the 'real child' and complex grief reactions have all been documented with Australian families (Richardson et al, 2013). Not only are the varied losses ambiguous, each family member can experience the loss and grief differently, possibly leading to further family conflict (Young, 2004). Furthermore, having a child live away from home exacerbates the experiences of grief and loss not only during the inpatient stay, but prior to it.…”
Section: The Parent's Experience Of Their Child's Mental Illnessmentioning
confidence: 99%
“…The areas of non-finite loss and disenfranchised grief are topics that are notably lacking in the child and adolescent mental health literature. As Young (2004) argues, a medicalised environment could have repercussions for those experiencing such latent pain:…”
Section: The Parent's Experience Of Their Child's Mental Illnessmentioning
confidence: 99%